Pelatihan Penulisan Naskah Ilmiah Jurnal Investigasi Volume 3 Nomor 1 Maret – Juni 2022 bagi Guru-guru se Kota Tangerang Selatan - Gatot Kusjono; Suprianto Suprianto; Syamruddin Syamruddin (Indonesian Journal of Society Engagement, 2022)
Community service activities Scientific Manuscript Writing Training Journal Investigation Volume 3 Number 1 March-June 2022 For Teachers throughout South Tangerang City aims to help elementary / junior high school / junior high school / high school / vocational school teachers in South Tangerang City in writing scientific manuscripts that will be published in journals with ISSN. The training method is carried out using the method of assistance, discussion, workshop and technical guidance (bimtek) of writing scientific manuscripts in accordance with journal manuscript standards. The training results were obtained as many as 8 elementary school teacher manuscripts (62%), 3 junior high school teacher manuscripts (23%), and 2 high school / vocational school teacher manuscripts (15%) published in the journal INVESTIGATION Volume 3 Number 1 March-June 2022. The publication of teachers' scientific manuscripts in the journal INVESTIGATIVE is certainly very helpful for teachers in fulfilling the obligation to journalize their scientific manuscripts, so that they are not constrained in increasing classes or positions.